2001
DOI: 10.1016/s1352-2310(01)00341-7
|View full text |Cite
|
Sign up to set email alerts
|

Variability-lifetime relationship of VOCs observed at the Sonnblick Observatory 1999—estimation of HO-densities

Abstract: An extensive dataset of VOC measurements was collected at the Sonnblick Observatory, Austria (3106 m) in Fall/ Winter 1999/2000, showing high mixing ratios of anthropogenic and biogenic VOCs at this high altitude site due to upward mixing of air masses (Geophys. Res. Lett. 2F (2001) 507). Here we give an interpretation of proton-transferreaction (PTR-MS) mass scans obtained in November 1999 based on fragmentation data, GC-PTR-MS analysis and the variability-lifetime relationship, described by the power law, sð… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 44 publications
2
42
1
Order By: Relevance
“…At the TT34 rainforest site, ecosystem-scale fluxes were directly calculated from the PTR-MS measurements using the method of virtual disjunct eddy covariance (vDEC) (Karl et al, 2001;Fig. 4).…”
Section: Sites Dominated By Biogenic Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the TT34 rainforest site, ecosystem-scale fluxes were directly calculated from the PTR-MS measurements using the method of virtual disjunct eddy covariance (vDEC) (Karl et al, 2001;Fig. 4).…”
Section: Sites Dominated By Biogenic Emissionsmentioning
confidence: 99%
“…Due to the standard operation conditions of the PTR-MS under our measurement conditions, we neglected water clusters as they are regarded to be insignificant (McKinney et al, 2011;. To summarise these issues, we note that several studies have concluded m/z 73 to originate from MEK only (Bourtsoukidis et al, 2014b;De Gouw et al, 1999Holzinger et al, 2000;Karl et al, 2001Karl et al, , 2005aKim et al, 2015;Millet et al, 2015;Steeghs et al, 2004). Based on these considerations and the similarity of magnitudes measured by the PTR-MS as compared with the GC results, we assume m/z 73 is representative of the atmospheric MEK present.…”
Section: Ptr-ms Measurementsmentioning
confidence: 99%
“…From these studies, it was proposed that the coefficient b, the dependence of variability on lifetime, reflects the importance of the source/sink budget in the regional variability of the studied species and varies from b=0 being close to the sources to b=0.5 in remote locations. Since these first studies, the variability concept has been applied to a number of datasets and has proved useful in ascertaining the consistency and quality of measurements and for the estimation of OH concentrations (Williams et al, 2000;Williams et al, 2001, Karl et al, 2001.…”
Section: Relationship Of Variability and Lifetime Of Compoundsmentioning
confidence: 99%
“…PTR-MS is now used in many branches of atmospheric chemistry research, including air quality monitoring (e.g. Karl et al, 2001aKarl et al, , 2003aKarl et al, , 2003bde Gouw et al, 2003), flux measurements (e.g. Holzinger et al, 1999;Karl et al, 2001b;Grabmer et al, 2004;Spirig et al, 2005), and oxidation studies (e.g.…”
Section: Introductionmentioning
confidence: 99%